Assessment of Alertness and Cognitive Performance of Closed Circuit Rebreather Divers With the Critical Flicker Fusion Frequency Test in Arctic Diving Conditions - Piispanen, Wilhelm W.; Lundell, Richard V.; Tuominen, Laura J.; Räisänen-Sokolowski, Anne K. (Frontiers in Physiology, 2021)
Introduction Cold water imposes many risks to the diver. These risks include decompression illness, physical and cognitive impairment, and hypothermia. Cognitive impairment can be estimated using a critical flicker fusion frequency (CFFF) test, but this method has only been used in a few studies conducted in an open water environment. We studied the effect of the cold and a helium-containing mixed breathing gas on the cognition of closed circuit rebreather (CCR) divers. Materials and Methods 23 divers performed an identical dive with controlled trimix gas with a CCR-device in an ice-covered quarry. They assessed their thermal comfort at four timepoints during the dive. In addition, their skin temperature was measured at 5-minute intervals throughout the dive. The divers performed the CFFF test before the dive, at target depth, and after the dive. Results A statistically significant increase of 111.7% in CFFF-values were recorded during the dive compared to the pre-dive values (P<0.0001). The values returned to the baseline after surfacing. There was a significant drop in the divers’ skin temperature of 0.48 °C every 10 minutes during the dive (P<0.001). The divers’ subjectively assessed thermal comfort also decreased during the dive (P=0.01). Conclusion Our findings showed that neither extreme cold water nor helium-containing mixed breathing gas had any influence on the general CFFF profile described in previous studies from warmer water and where divers used other breathing gases. We hypothesize that cold water diving and helium containing breathing gases do not in these diving conditions cause clinically relevant cerebral impairment. Therefore, we conclude that CCR diving in these conditions is safe from the perspective of alertness and cognitive performance.